Optimization, compositional analysis, and characterization of exopolysaccharides produced by multi-metal resistant Bacillus cereus KMS3-1. (1st January 2020) - Krishnamurthy, Mathivanan; Jayaraman Uthaya, Chandirika; Thangavel, Mathimani; Annadurai, Vinothkanna; Rajendran, Rajaram; Gurusamy, Annadurai
Highlights: Multi-metal resistant bacteria was isolated from surface sediment and identified. Isolate S2-2 and S3-2 could grow till 30 and 55 ppm respectively in metal consortium. CCD showed 5 g/L sucrose and 30 g/L yeast extract are optimal for greater EPS yield. FTIR, TLC and HPLC revealed that EPS are heteropolysaccharide. Strong emulsifying and flocculation activity was observed with extracted EPS. Abstract: The isolation, screening, and identification of multi-metal resistant (Cd, Cu, Pb, and Zn) bacteria from polluted coastal sediment samples were performed. In this study, the isolates S2-2 and S3-2 had higher multi-metal resistance and were identified as Pseudomonas pachastrellae KMS2-2 and Bacillus cereus KMS3-1, respectively. One-variable-at-a time approach suggested that optimum conditions for exopolysaccharides (EPS) production were pH 7.0, incubation time 120 h, 5 g/L sucrose, and 10 g/L yeast extract. Further, optimization by central composite design revealed that the optimum concentrations of sucrose and yeast extract for higher EPS production (8.9 g/L) were 5 g/L, and 30 g/L, respectively. Heteropolysaccharide nature of EPS determined by FTIR, TLC, and HPLC analysis, consist of mannose, rhamnose, glucose, and xylose. In addition, EPS showed strong emulsifying and flocculation activity. Results suggested the potential EPS-producing multi-metal resistant Bacillus cereus KMS3-1 could be used in biotechnological and industrial application, especially metal removal.